A Posttraumatic Distal Radius Allograft: 10 Years Follow-Up - Lauri, Giulio; Biondi, Marco; Roselli, Giuliana; Bigazzi, Prospero (Journal of Wrist Surgery, 2018)
Background Wrist osteoarthritis is a common disease often resulting from malunited fractures of the distal radius. The primary treatment purpose is to provide pain relief, while maintaining strength and mobility whenever possible. In a patient presenting a posttraumatic degeneration of the wrist, deciding which surgical technique, which joints to sacrifice and which to preserve is crucial to optimizing the outcome.Case Description We describe a 10-year follow-up of an osteoarticular allograft of the distal radius proposed to treat an isolated distal radius posttraumatic degeneration. The patient was young and active. No or slight articular degeneration of the carpal rows was present. The surgical technique was based on a periarticular step-cut that allowed the preservation of the dorsal capsule and the maximum contact between the bone and the allograft.Literature Review In the literature, the allograft of the radius is described as a solution to an oncologic problem. Considering a posttraumatic scenario other techniques are usually performed. However, compared with artificial interbody fusion devices and prosthetic implants, structural bone allograft retains an advantage in biologic performance. It has osteoconductive properties and is similar to native tissues providing a progressive incorporation by the host.Clinical Relevance This surgical technique provide a metaphyseal step-cut able to ensure a secure stabilization and a wide contact surface between the allograft and the native bone. Integration of the allograft with good functional and radiological outcome seen after 10 years supports this technique.
Keywords: distal radius allograft; wrist arthritis; distal radius degeneration; distal radius fracture; radioscapholunate